Wigner functions and Moyal equation in noncommutative space - Ma, Kai; Li, Kang; Wang, Jian-Hua (Zhejiang da xue xue bao. Journal of Zhejiang University. Sciences edition. Li xue ban, 2011)
Firstly this paper makes a brief review of the Moyal equation and Wigner Functions in commutative space. Then, the Moyal equation which the Wigner Functions support is introduced in Non-communacative phase space. Finally, by redefining the raising and lowering operator, Wigner functions for the coherent state of two-dimensional Harmonic oscillators are obtained.